Faktor-faktor yang Mempengaruhi Nasabah Menggunakan Produk BNI Tapenas Pada PT. Bank Negara Indonesia (Persero) Tbk KCP Puri Kencana Makassar - B, Ceskakusumadewi; Muchsidin, Feronica Fungky; Muchsidin, Murdin; Panus, Panus; Labolo, Sabrina (LPPM STIE Tri Dharma Nusantara - Makassar, 2024)
The aim of this study is to identify the most dominant factor influencing customers' purchasing decisions regarding the BNI TAPENAS product at PT. Bank Negara Indonesia (Persero) Tbk, KCP Puri Kencana Makassar. This research involved a sample of 100 customer respondents selected using the accidental sampling technique. Based on the analysis of 15 factors, five core factors were identified: (1) the savings facility factor, which emerged as the most influential factor; (2) the social status factor, ranked as the second most significant; (3) the bank condition factor, ranked third; (4) the psychological factor, ranked fourth; and (5) the cultural factor, ranked fifth.